Celestial IR divergences in general most-subleading-color gluon and gravity amplitudes - Nastase, Horatiu [UNESP]; Rojas, Francisco; Rubio, Carlos (Springer Nature, 2022)
Gluon amplitudes at most-subleading order in the 1/N expansion share a remarkable simplicity with graviton amplitudes: collinear divergences are completely absent in both and, as a consequence, their full IR behavior arises from soft gluon/graviton exchange among the external states. In this paper we study the effect of all-loop IR divergences of celestial most-subleading color gluon amplitudes and their similarities with the celestial gravity case. In particular, a simple celestial exponentiation formula for the dipole part can be written. We also analize how this exponentiation is modified by non-dipole contributions. Finally we also show that, in the Regge limit, the soft factor satisfies the Knizhnik-Zamolodchikov equation hinting at the possibility that, in this limit, an effective Wess-Zumino-Witten model would describe the dynamics of the infrared sector.
Keywords: Conformal Field Theory; Scattering Amplitudes